ENHANCING WRITING ABILITY BY USING STUDENTS' PERSONAL EXPERIENCE IN RECOUNT TEXT AT XI GRADE OF SMK NEGERI 7 MBD - Lewier, Winnie Mariana; S.S, M.Hum, Monica; Tiwery, Yulina (Koli Journal : English Language Education, 2024)
This research aims to examine whether the use of students' personal experiences can improve their ability to write recount texts and to determine students' responses to the application of this strategy. The research was conducted at SMK Negeri 7 MBD with research subjects of 15 class XI students. This research used a Classroom Action Research (PTK) design which was carried out in two cycles, each consisting of five meetings. Data was collected through observation, questionnaires and written tests. The research results show that the use of personal experience as a learning strategy can improve students' writing skills in recount text. The students' average score increased from 57.8 on the pre-test to 68.7 on post-test I, and 81.8 on post-test II. The success indicator is defined as 75% of students achieving a minimum score of 70 or more. The percentage of students who achieved a completeness score was 20% on the pre-test, 60% on post-test I, and 100% on post-test II. This proves that the target of success has been achieved. In addition, the questionnaire results showed a student satisfaction level of 80%, which was categorized as "good". Based on these results, it can be concluded that the use of personal experience can significantly improve students' writing skills in recount texts. Keywords: Writing, Personal Experience, Recount Text.